2013
DOI: 10.5424/sjar/2013114-4210
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy against the hazelnut weevil, Curculio nucum and short-term persistence of entomopathogenic nematodes

Abstract: The hazelnut weevil, Curculio nucum L. (Coleoptera: Curculionidae) is a pest affecting hazelnut orchards in Europe, with an important economical repercussion. Its potential control, short-term f ield persistence and the vertical distribution of native entomopathogenic nematode strains were tested in Muntanyes de Prades, Tarragona (NE Iberian Peninsula) over two consecutive years. Steinernema feltiae strain D114, Steinernema sp. strain D122 and Heterorhabditis bacteriophora strain DG46 were used in summer and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the Mediterranean region, because of the spread of exotic palm weevils, promising experiments to contain the spread of the weevil Rynchophorus ferrugineus with entomopathogenic EPN nematodes have been carried out in several countries, such as Egypt, Spain, and Italy ( Figure 13 ). Other applications of beneficial nematodes have been effective in controlling sciarid dipteran in ornamental nurseries and mushroom farms, the weevil curculionid Curculio nucum on hazels ( 103 ), the thrips Frankliniella occidentalis ( 104 ), the lepidopteran Tuta absoluta on tomato, the chrysomelid Diabrotica virgifera on corn ( 105 ), and slugs and snails in horticulture, with the latter case involving the use of the specific nematode Phasmarhabditis hermaphrodita ( 49 ). Entomopathogenic nematodes have also been found to be effective against xylophagous insects residing in cryptic habitats, such as Capnodis tenebrionis , Arhopalus syriacus , Cossus cossus , and Parahypopta caestrum ( 106 ).…”
Section: Biological Control Strategies Using Epnsmentioning
confidence: 99%
“…In the Mediterranean region, because of the spread of exotic palm weevils, promising experiments to contain the spread of the weevil Rynchophorus ferrugineus with entomopathogenic EPN nematodes have been carried out in several countries, such as Egypt, Spain, and Italy ( Figure 13 ). Other applications of beneficial nematodes have been effective in controlling sciarid dipteran in ornamental nurseries and mushroom farms, the weevil curculionid Curculio nucum on hazels ( 103 ), the thrips Frankliniella occidentalis ( 104 ), the lepidopteran Tuta absoluta on tomato, the chrysomelid Diabrotica virgifera on corn ( 105 ), and slugs and snails in horticulture, with the latter case involving the use of the specific nematode Phasmarhabditis hermaphrodita ( 49 ). Entomopathogenic nematodes have also been found to be effective against xylophagous insects residing in cryptic habitats, such as Capnodis tenebrionis , Arhopalus syriacus , Cossus cossus , and Parahypopta caestrum ( 106 ).…”
Section: Biological Control Strategies Using Epnsmentioning
confidence: 99%
“…All of these semi-field trials were conducted in plastic tubes or buckets buried into the soil where a known number of larvae of C. nucum were introduced. While Kuske et al (2005) and Peters, Sarraquigne, Blum, and Kuske (2007) achieved efficacies between 0 and 63 % using commercial EPNs, Batalla-Carrera et al (2013a) obtained efficacies between 34 and 88 % using EPN species isolated in the soil of hazelnut orchards. This could be highlighting the importance of the use of native species, as these isolates may be better adapted or prepared to infect a particular host that cohabits in the same location.…”
Section: Semi-field Trialsmentioning
confidence: 98%
“…All EPNs showed the capacity of controlling larvae both in spring, when C. nucum is overwintering, and during the summer when they are burying in the soil, because EPNs have the capacity to find and invade overwintering stages of this insect at any depth. Thus, Batalla-Carrera et al (2013a) concluded that EPNs can effectively reduce C. nucum populations and suggested that a spring application could be an alternative to summer application in order to minimize negative abiotic factors and improve EPN persistence.…”
Section: Semi-field Trialsmentioning
confidence: 99%
“…C. nucum larvae, which feed on hazelnuts ( Fig. 1), are found throughout most of Europe and Asia [3,4]. In recent years, C. nucum has developed medium to high levels of resistance to the main chemical pesticides used in northeast China, resulting in a need for increased dosage and repeated applications of these pesticides.…”
Section: Introductionmentioning
confidence: 99%